2019
DOI: 10.1101/781849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Components of the endocytic and recycling trafficking pathways interfere with the integrity of theLegionella-containing vacuole

Abstract: SummaryLegionella pneumophila requires the Dot/Icm translocation system to replicate in a vacuolar compartment within host cells. Strains lacking the translocated substrate SdhA form a permeable vacuole during residence in the host cell, exposing bacteria to the host cytoplasm. In primary macrophages, mutants are defective for intracellular growth, with a pyroptotic cell death response mounted due to bacterial exposure to the cytosol. To understand how SdhA maintains vacuole integrity during intracellular grow… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 55 publications
5
9
0
Order By: Relevance
“…For EEA1 and CIMPR, there was a significant increase in LCV association for each marker after infection with a DsdhA strain for 3hrs when compared to WT. The increase was particularly striking with EEA1, supporting our previous analysis of the behavior of DsdhA strains with murine bone marrow-derived macrophages (Anand et al, 2020) (Fig. 7A).…”
Section: Sdha Inhibits the Accumulation Of Ocrl-dependent Endosomal Tsupporting
confidence: 89%
See 3 more Smart Citations
“…For EEA1 and CIMPR, there was a significant increase in LCV association for each marker after infection with a DsdhA strain for 3hrs when compared to WT. The increase was particularly striking with EEA1, supporting our previous analysis of the behavior of DsdhA strains with murine bone marrow-derived macrophages (Anand et al, 2020) (Fig. 7A).…”
Section: Sdha Inhibits the Accumulation Of Ocrl-dependent Endosomal Tsupporting
confidence: 89%
“…RNAi depletion of Rab5, Rab11, and Rab8, all GTPases involved in endocytic and recycling pathways, partially reverses loss of vacuole integrity observed in sdhA mutants. Consistent with these results, the absence of SdhA results in LCV accumulation of EEA1 and Rab11FIP1, downstream effectors of these GTPases (Anand et al, 2020;Christoforidis et al, 1999;Hales et al, 2001). Therefore, it is likely that SdhA interferes with components of the early endocytic network that are likely to disrupt vacuole integrity.…”
Section: The Intracellular Growth Of L Pneumophila Depends On the Cosupporting
confidence: 66%
See 2 more Smart Citations
“…Alternatively, VAMP3 may mediate the delivery of an anti-microbial cargo to PV harboring L. amazonensis, thereby limiting parasite replication and PV expansion. Clearly, our study revealed a novel role for VAMP3 in the control of communal PV expansion and L. amazonensis replication, highlighting the fact that depending of the pathogen, a molecule involved in regulating vesicular trafficking and membrane fusion events may either favor or impair pathogen growth, as recently described for Rab11 in the context of L. pneumophila infection (65). Further studies will be aimed at elucidating the underlying mechanism(s).…”
Section: Vamp3 Negatively Regulates Antigen Cross-presentationsupporting
confidence: 59%